Sequence Variation in Malayan Tapir (Tapirus indicus) Inferred Using Partial Sequences of the Cytochrome b Segment of the Mitochondrial DNA - Jeffrine Japning, Rovie-Ryan; Carl, Traeholt; Edward, Marilyn-Jaoi; Zainal Zahari, Zainuddin; Khairiah, Mohd Shariff; Sivananthan, Elagupillay; M. Y., Mohd. Farouk; Aniqa Akhtar, Abdullah; C. S., Cornelia (Department of Wildlife and National Parks, 2008)
Comparison of 321 bp long mtDNA cytochrome b sequences of wild and captive Malayan tapir (Tapirus indicus)revealed low variation among the individuals investigated. Phylogenetic analyses using distance (neighbor-joining) analysis supported the monophyletic status of the Malayan tapir. Two haplotypes were identified out of 13 Malayan tapir analyzed.